Absence of hepatitis delta infection in a large rural HIV cohort in Tanzania. (May 2016) - Winter, Annja; Letang, Emilio; Vedastus Kalinjuma, Aneth; Kimera, Namvua; Ntamatungiro, Alex; Glass, Tracy; Moradpour, Darius; Sahli, Roland; Le Gal, Frédéric; Furrer, Hansjakob; Wandeler, Gilles; ,
Highlights: Hepatitis delta virus (HDV) infection is very rare in rural Tanzania. False-positive screening results for HDV are common. Each positive HDV screening test result should be confirmed by a second test. More research is needed to understand the epidemiology of HDV infection in Sub-Saharan Africa. Summary: Objectives: The epidemiological and clinical determinants of hepatitis delta virus (HDV) infection in Sub-Saharan Africa are ill-defined. The prevalence of HDV infection was determined in HIV/hepatitis B virus (HBV) co-infected individuals in rural Tanzania. Methods: All HBV-infected adults under active follow-up in the Kilombero and Ulanga Antiretroviral Cohort (KIULARCO) were screened for anti-HDV antibodies. For positive samples, a second serological test and nucleic acid amplification were performed. Demographic and clinical characteristics at initiation of antiretroviral therapy (ART) were compared between anti-HDV-negative and -positive patients. Results: Among 222 HIV/HBV co-infected patients on ART, 219 (98.6%) had a stored serum sample available and were included in the study. Median age was 37 years, 55% were female, 46% had World Health Organization stage III/IV HIV disease, and the median CD4 count was 179 cells/μl. The prevalence of anti-HDV positivity was 5.0% (95% confidence interval 2.8–8.9%). There was no significant predictor of anti-HDV positivity. HDV could not be amplified in any of the anti-HDV-positive patients and the second serological test was negative in all of them. Conclusions: No confirmed case of HDV infection was found among over 200 HIV/HBV co-infected patients in Tanzania. As false-positive serology results are common, screening results should be confirmed with a second test.